Evaluasi Kinerja Bundaran Bersinyal Polres Dumai: Studi Kasus pada Bundaran Polres di Kota Dumai, Riau - Mizan Shiddieqy; Muhammad Idham (Racic : Rab Construction Research, 2025)
The signalized roundabout at Polres Kota Dumai plays a vital role in regulating traffic flow in the city. This study evaluates the roundabout’s performance using the Indonesian Highway Capacity Guidelines (PKJI) 2023 and the traffic simulation software PTV VISSIM. Parameters analyzed include traffic volume, roundabout capacity, level of service (LOS), and traffic signal cycle duration. The evaluation results show that the current condition has a LOS in categories B–C, indicating stable traffic flow. A five-year projection shows an increase in traffic volume, but the degree of saturation (DS) remains below the safe threshold (DS < 0.85). However, in the ten-year projection, the DS on the east and west approaches exceeds the limit, suggesting the need for geometric improvements, such as reducing the median and widening the road. This study highlights the importance of evaluating the performance of signalized roundabouts for more efficient transportation planning and to prevent future congestion.